2001
DOI: 10.1080/003655201300192030
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density Reduction in Patients with Crohn Disease and Associations with Demographic and Disease Variables: Cross-sectional Data from a Population-based Study

Abstract: The spine and hip BMD reduction of 6%-8% is similar to that found in a comparable population-based study performed in another area in Norway. Among the disease-related variables tested for, only the use of prednisolone was independently associated with BMD reduction. However, the BMD reduction measured in this study indicates that disease-related mechanisms are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…However, in Canada relapses of Crohn disease peaked in autumn and winter, with a summer trough [22]. Researchers in Denmark [23], southern Norway [24] and Toronto, Canada [25] have recently reported a negative association of bone mineral density with age, at least in some locations of DEXA measurements. This is in partial agreement with the nonsignificant decrease of T-score with age in patients with active disease in our study, but not quite with the borderline significant increase of T-score in patients with inactive disease up to age 35 followed by its borderline significant decrease thereafter.…”
Section: Discussionmentioning
confidence: 96%
“…However, in Canada relapses of Crohn disease peaked in autumn and winter, with a summer trough [22]. Researchers in Denmark [23], southern Norway [24] and Toronto, Canada [25] have recently reported a negative association of bone mineral density with age, at least in some locations of DEXA measurements. This is in partial agreement with the nonsignificant decrease of T-score with age in patients with active disease in our study, but not quite with the borderline significant increase of T-score in patients with inactive disease up to age 35 followed by its borderline significant decrease thereafter.…”
Section: Discussionmentioning
confidence: 96%
“…16,21,24,26,27 However, patients who had undergone ileal resection had higher rates of osteoporosis than patients who did not undergo small bowel resection. 21 Some studies found an association between bowel resection and lower BMDs, 14,16,28,29 whereas the others found no association between the two. 18,23,26,30 Other markers of disease activity that were associatedwith reduced BMD included hypoalbuminemia, 14,31 high white cell counts, 18 high platelet counts, 18 increased bowel movements, 32 high interleukin-6 levels, 19 and high C-reactive protein 26 levels.…”
mentioning
confidence: 97%
“…The fracture rate was the same in patients with Crohn's disease and those with ulcerative colitis. Haugeberg et al [39] documented a 6% to 8% reduction of BMD in patients with Crohn's disease compared with control subjects, and the use of corticosteroids was the only disease-related factor associated with low BMD. Schoon et al [40] found a 45% incidence of osteopenia and 13% incidence of osteoporosis in a Dutch population-based study of 119 patients with Crohn's disease.…”
Section: Gastrointestinal Disorders Associated With Metabolic Bone DImentioning
confidence: 96%